Clinical Approach to Autoimmune Epilepsy - Jang, Yoonhyuk; Kim, Dong Wook; Yang, Kwang Ik; Byun, Jung-Ick; Seo, Jong-Geun; No, Young Joo; Kang, Kyung Wook; Kim, Daeyoung; Kim, Keun Tae; Cho, Yong Won; Lee, Soon-Tae (Journal of clinical neurology (Seoul, Korea), 2020)
Autoimmune epilepsy is a newly emerging area of epilepsy. The concept of "autoimmune" as an etiology has recently been revisited thanks to advances in autoimmune encephalitis and precision medicine with immunotherapies. Autoimmune epilepsy presents with specific clinical manifestations, and various diagnostic approaches including cerebrospinal fluid analysis, neuroimaging, and autoantibody tests are essential for its differential diagnosis. The diagnosis is often indeterminate despite performing a thorough evaluation, and therefore empirical immunotherapy may be applied according to the judgment of the clinician. Autoimmune epilepsy often manifests as new-onset refractory status epilepticus (NORSE). A patient classified as NORSE should receive empirical immunotherapy as soon as possible. On the other hand, a morecautious, stepwise approach is recommended for autoimmune epilepsy that presents with episodic events. The type of autoimmune epilepsy is also an important factor to consider when choosing from among various immunotherapy options. Clinicians should additionally take the characteristics of antiepileptic drugs into account when using them as an adjuvant therapy. This expert opinion discusses the diagnostic and treatment approaches for autoimmune epilepsy from a practical point of view.Autoimmune epilepsy is a newly emerging area of epilepsy. The concept of "autoimmune" as an etiology has recently been revisited thanks to advances in autoimmune encephalitis and precision medicine with immunotherapies. Autoimmune epilepsy presents with specific clinical manifestations, and various diagnostic approaches including cerebrospinal fluid analysis, neuroimaging, and autoantibody tests are essential for its differential diagnosis. The diagnosis is often indeterminate despite performing a thorough evaluation, and therefore empirical immunotherapy may be applied according to the judgment of the clinician. Autoimmune epilepsy often manifests as new-onset refractory status epilepticus (NORSE). A patient classified as NORSE should receive empirical immunotherapy as soon as possible. On the other hand, a morecautious, stepwise approach is recommended for autoimmune epilepsy that presents with episodic events. The type of autoimmune epilepsy is also an important factor to consider when choosing from among various immunotherapy options. Clinicians should additionally take the characteristics of antiepileptic drugs into account when using them as an adjuvant therapy. This expert opinion discusses the diagnostic and treatment approaches for autoimmune epilepsy from a practical point of view.